The Effect of a Glass Ceramic Insert in Sandwich Technique on Microleakage in Class II Composite Resin Restorations - Hila Hajizadeh; Saied Mostafa Moazzami; Nasrin Sarabi; Sara Majidinia (Mashhad University of Medical Sciences, 2015)
Introduction: The aim of the present study was to evaluate the effect of glass ceramic insert in the sandwich technique to reduce microleakage in class II composite resin restorations. Methods: Sixty sound human upper second premolars were selected and randomly divided into six groups (n=10). Class II box-only cavities were prepared in distal aspects of each tooth with gingival margin located approximately 0.5 mm below the CEJ. Group A (Control) was restored incrementally with Tetric Ceram and a total-etch bonding technique. Group B and C were restored with sandwich technique using a compomer (Compoglass F) or flowable composite resin (Tetric Flow) as the lining material at gingival floor, respectively. Group D, E and F were represented in the same way as group A, B and C and a glass ceramic insert was added to the composite bulk. The specimens were thermo-mechanically cycled, and then immersed in 0.5 % basic fuschin for 24 hours. Dye penetration was detected using a sectioning technique. Results: No significant difference was found between total-etch bonding and sandwich techniques. The placement of an insert caused an increase in   microleakage in all groups significantly (P < 0.05). Group D (no liner/ with glass insert) showed the highest amount of microleakage and Group A (no liner/ without glass insert) resulted in the lowest amount of total microleakage. Conclusion: Placement of glass ceramic insert could not decrease gingival leakage. According to the limitation of this study a composite resin restorations with incremental technique is recommended